If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -9 = 4y + -12 Reorder the terms: -9 + 7y = 4y + -12 Reorder the terms: -9 + 7y = -12 + 4y Solving -9 + 7y = -12 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -9 + 7y + -4y = -12 + 4y + -4y Combine like terms: 7y + -4y = 3y -9 + 3y = -12 + 4y + -4y Combine like terms: 4y + -4y = 0 -9 + 3y = -12 + 0 -9 + 3y = -12 Add '9' to each side of the equation. -9 + 9 + 3y = -12 + 9 Combine like terms: -9 + 9 = 0 0 + 3y = -12 + 9 3y = -12 + 9 Combine like terms: -12 + 9 = -3 3y = -3 Divide each side by '3'. y = -1 Simplifying y = -1
| 5r+20-7r=-16 | | -12-2x=-2(x+5) | | s=550 | | 6x+8x+10x=180 | | 12=3(6t+1) | | -2.8=-0.56(m+8) | | 7(4y-5)+3(5y+4)= | | 3m-17=52 | | 3(6x+24)=18x+72 | | 2q(q-6)=0 | | 2=2v-2 | | 6(1-4y)-5y=-8(3+4y) | | 6x+9y=2 | | 2k-4=12 | | 4-3x=-3+4x | | 3.5x+1.25= | | -25k=-150 | | 82=-65-x | | -(7x+6)=-3(1+2x) | | 4m^2-12a=-8 | | 7b+3-4b=3-3(-b+4) | | 7x+9-3x=25 | | 71=23-4x | | -4x+4-2x=-s(3x-3) | | 2x^2-3y^2+8x-60y-304=0 | | 3x+48=5 | | -2+10+4= | | 3(t+6)= | | -45y=-90 | | 4-6b=40 | | -457=-90 | | 4x-10=7x-16 |